Retrovirus-induced interference with collagen I gene expression in Mov13 fibroblasts is maintained in the absence of DNA methylation. - Chan, H (1991)
We have studied the role of DNA methylation in repression of the murine alpha 1 type I collagen (COL1A1) gene in Mov13 fibroblasts. In Mov13 mice, a retroviral provirus has inserted into the first intron of the COL1A1 gene and blocks its expression at the level of transcriptional initiation. We found that regulatory sequences in the COL1A1 promoter region that are involved in the tissue-specific regulation of the gene are unmethylated in collagen-expressing wild-type fibroblasts and methylated in Mov13 fibroblasts, confirming and extending earlier observations. To directly assess the role of DNA methylation in the repression of COL1A1 gene transcription, we treated Mov13 fibroblasts with the demethylating agent 5-azacytidine. This treatment resulted in a demethylation of the COL1A1 regulatory sequences but failed to activate transcription of the COL1A1 gene. Moreover, the 5-azacytidine treatment induced a transcription-competent chromatin structure in the retroviral sequences but not in the COL1A1 promoter. In DNA transfection and microinjection experiments, we found that the provirus interfered with transcriptional activity of the COL1A1 promoter in Mov13 fibroblasts but not in Xenopus laevis oocytes. In contrast, the wild-type COL1A1 promoter was transcriptionally active in Mov13 fibroblasts. These experiments showed that the COL1A1 promoter is potentially transcriptionally active in the presence of proviral sequences and that Mov13 fibroblasts contain the trans-acting factors required for efficient COL1A1 gene expression. Our results indicate that the provirus insertion in Mov13 can inactivate COL1A1 gene expression at several levels. It prevents the developmentally regulated establishment of a transcription-competent methylation pattern and chromatin structure of the COL1A1 domain and, in the absence of DNA methylation, appears to suppress the COL1A1 promoter in a cell-specific manner, presumably by assuming a dominant chromatin structure that may be incompatible with transcriptional activity of flanking cellular sequences.